The relation between Foreign Language Enjoyment, subjective well-being, and perceived stress in multilingual students - Ergun, Anna Lia Proietti; Demirdag, Hande Ersoz (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
In the last ten years, positive emotion in foreign language learning has been increasingly investigated in many research areas, including Foreign Language Enjoyment (FLE). FLE has been defined as a positive emotion felt when an individual's psychological needs are met. This study investigates the relationship between perceived levels of Subjective Well-Being (SWB) and Stress (PS), as well as the degree of multilingualism (DM) and their effect on FLE when learning an additional language. The data were collected from 68 students (35 trilingual and 33 bilingual) who were learning an additional language (Italian or French). Statistical analyses showed that SWB and PS were unrelated. The strongest predictors of the FLE was SWB, with PS having a small but significant effect. Trilingual subjects were found to have significantly more FLE, whereas there was no statistically significant difference for SWB and PS. The findings are discussed in light of previous research on FLE, which confirms that SWB and DM, as well as a low level of stress, play an important role in enjoying learning a new language. The implication of this study is discussed both for language teaching and language policy formulation.
Keywords: Multilingualism; well-being; perceived stress; foreign language acquisition; POSITIVE PSYCHOLOGY; EMOTIONS; ANXIETY; BENEFITS; BROADEN; FLOW; Linguistics